Blood lactate clearance at the OBLA intensity - Richardson, M. T.; Rinehardt, K. F.; Bouchier, N. B.; Zoernik, D.; Campbell, D.; Cordill, M. R. (Medicine & Science in Sports & Exercise, 1993)
In male swimmers (N = 15) onset of blood lactate accumulation (OBLA) occurred at 51% of maximal resistance in tethered swimming and 70% of maximal heart rate. OBLA pace removes lactate fastest and in less than 15 min. It was found that recovery was fastest when actively recovering at OBLA pace. Implication: In swimming, recovery is facilitated by continuous swimming at a velocity that was equal to that which produced lactate accumulation (OBLA).